2007
DOI: 10.1200/jco.2007.12.4180
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist Communication About Emotion During Visits With Patients With Advanced Cancer

Abstract: Oncologists encountered few empathic opportunities and responded with empathic statements infrequently. Empathic responses were more prevalent among younger oncologists and among those who were self-rated as socioemotional. To reduce patient anxiety and increase patient satisfaction and adherence, oncologists may need training to encourage patients to express emotions and to respond empathically to patients' emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
240
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(262 citation statements)
references
References 27 publications
13
240
2
7
Order By: Relevance
“…Regarding source of emotion (i.e. cues elicited by patients versus clinicians), Pollack et al found that, when patients initiated negative emotions, oncologists responded with a terminator statement 73% of the time, to discourage further disclosure of emotions [15]. Similar findings were reported in more recent studies, where a multilevel approach was adopted to respect the clustered nature of the data contained within the consultation [16,17].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Regarding source of emotion (i.e. cues elicited by patients versus clinicians), Pollack et al found that, when patients initiated negative emotions, oncologists responded with a terminator statement 73% of the time, to discourage further disclosure of emotions [15]. Similar findings were reported in more recent studies, where a multilevel approach was adopted to respect the clustered nature of the data contained within the consultation [16,17].…”
Section: Introductionsupporting
confidence: 62%
“…utterance) level, source [15][16][17], type [18,19] and timing [17,19] of emotional expression were found to be important predictors for clinicians' responses. Regarding source of emotion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…When physicians focus on psychosocial aspects of care, use open-ended questions, listen actively, and make empathic statements, their patients are more likely to express distress and concerns [36,48]. An analysis of the oncologists' behaviors in the recordings used in this study is reported elsewhere; in that analysis, oncologists responded empathically to patients' expressions of emotion less than one third of the time [42]. Research shows that when clinicians repeatedly miss patients' expressions of emotion, patients eventually cease to express emotion [56].…”
Section: Discussionmentioning
confidence: 99%
“…Given the methodology of our study, we cannot know how many patients were concerned about death and dying. However, past studies indicate that patients who described their concerns about symptoms and medical issues narrowly might have given a fuller account if their oncologists had responded empathically to their expressions of emotion [36,42].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, survey data indicate that oncologists from Western countries are more disclosive than those practicing in nonWestern countries [61], and that other factors such as sex [61], age [61], training in the communication of bad news [4,[69][70][71][72], and frequent requests from family members for non-disclosure [40,55,73] may affect attitudes and actual clinical behaviors.…”
mentioning
confidence: 99%